2007
DOI: 10.2135/cropsci2006.09.0565
|View full text |Cite
|
Sign up to set email alerts
|

Geostatistical Analysis of Dollar Spot Epidemics Occurring on a Mixed Sward of Creeping Bentgrass and Annual Bluegrass

Abstract: Dollar spot (Sclerotinia homoeocarpa F.T. Bennett) causes one of the most important diseases faced by golf course superintendents throughout the USA. Fungicides are effective, but fungicide resistance and regulation have restricted their use. Site‐specific application allows more judicious use of fungicides, but the spatial heterogeneity of dollar spot incidence has been unknown. An intensive study was designed to determine the spatial distribution of dollar spot incidence using geostatistical analysis. Dollar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Heavy reliance on synthetic fungicides has led to the development of fungicide resistant fungal populations (4), imposes a significant financial burden on the turfgrass manager (5), and increases the risk of human and on March 29, 2021 by guest http://aem.asm.org/ Downloaded from environmental contamination resulting from repeated chemical exposures (6). The development of dollar spot symptoms in uniformly managed turfgrass with nearly identical environmental conditions is often highly variable, even at a scale of several meters (7). It is unclear why dollar spot develops in such a variable manner, but plausible explanations include a link to hyperlocal variations in microbial antagonists or local variations in soil physical, chemical, or biological properties.…”
Section: Introductionmentioning
confidence: 99%
“…Heavy reliance on synthetic fungicides has led to the development of fungicide resistant fungal populations (4), imposes a significant financial burden on the turfgrass manager (5), and increases the risk of human and on March 29, 2021 by guest http://aem.asm.org/ Downloaded from environmental contamination resulting from repeated chemical exposures (6). The development of dollar spot symptoms in uniformly managed turfgrass with nearly identical environmental conditions is often highly variable, even at a scale of several meters (7). It is unclear why dollar spot develops in such a variable manner, but plausible explanations include a link to hyperlocal variations in microbial antagonists or local variations in soil physical, chemical, or biological properties.…”
Section: Introductionmentioning
confidence: 99%
“…Heavy reliance on synthetic fungicides has led to the development of fungicide resistant fungal populations (4), imposes a significant financial burden on the turfgrass manager (5), and increases the risk of human and environmental contamination resulting from repeated chemical exposures (6). The development of dollar spot symptoms is often highly variable within several meters distance, even in uniformly managed turfgrass with nearly identical environmental conditions (7). While it is not known why dollar spot symptoms develop in such a variable manner, one plausible explanation is a link to hyperlocal variations in microbial antagonists or variations in soil physical, chemical, or biological properties.…”
Section: Introductionmentioning
confidence: 99%
“…Geostatistical analysis of dollar spot epidemics demonstrated limited spread of this pathogen within a season, indicating that equipment does not contribute to spread of inoculum. Consequently, the authors concluded that epidemics initiated from individual clusters of infection centers [13] .…”
Section: Introductionmentioning
confidence: 99%